Application of Classical Fenton Process and Advanced Photo Electro Fenton Process for the Degradation of COD from Wood Processing Wastewater: A Comparative Study - Murat Solak (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, Chemical Oxygen Demand (COD) removal efficiency from wood processing wastewaters by Fenton Process (FP) and Photo Electro Fenton Process (PEFP) were examined. Important operating parameters such as pH, Fe+2 concentration/(amper for PEFP), H2O2 concentration and reaction time were optimized. Optimum operation conditions of the FP were pH 3.5, 1.4 gr/L Fe2+ concentration and 50 gr/L H2O2 concentration and 150 min. reaction time while they were pH 3.00, 9.99 mA/cm2 current density and 70 gr/L H2O2 concentration and 150 min reaction time in PEFP. At the optimum conditions, COD removal efficiency of FP and PEFP was 91% and 99%, respectively. Sludge production of FP was 20% higher than PEFP at the optimum conditions.